2019
DOI: 10.7150/jca.28218
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Enhances Endometrial Cancer Cells Proliferation by Upregulation of Prohibitin

Abstract: Estrogen plays an essential role in type I endometrial cancer cell proliferation. Despite great progresses in the etiology has been obtained in the past, however, the molecular mechanisms remain to be fully clarified. Prohibitin has been demonstrated involvement in multiple cancers' development. If it also contributes to estrogen-driven endometrial cancer proliferation is not clear. IHC assay result display that prohibitin overexpressed in endometrial cancer tissue and associated with the poor prognosis; Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Depletion of adapter protein of E3 ubiquitin ligase promotes endometrial cancer cell growth 22 . Inhibition of ubiquitination leads to stabilization, increases prohibition, and facilitates endometrial cancer cell proliferation 23 . In addition, deubiquitination is implicated in sensitization of endometrial cancer cells to estrogen 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of adapter protein of E3 ubiquitin ligase promotes endometrial cancer cell growth 22 . Inhibition of ubiquitination leads to stabilization, increases prohibition, and facilitates endometrial cancer cell proliferation 23 . In addition, deubiquitination is implicated in sensitization of endometrial cancer cells to estrogen 24 .…”
Section: Discussionmentioning
confidence: 99%
“…PHB is an independent prognostic factor for PDAC [18]. PHB overexpression is detected in endometrial cancer tissues and is linked to poor prognosis [19]. PHB protein is highly expressed in Wilms tumor specimens and is correlated with the tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, aberrant estrogen metabolism was also greatly involved in endometrial cancer growth and metastasis. [68][69][70] Zhang et al 25 first explored the association between FTO and estrogen in endometrial cancer, they found that β-estradiol (E2) up-regulated FTO expression, thus enhancing endometrial cancer cell proliferation, migration and invasion via activating phosphatidylinositol-3-kinase (PI3K)/protein kinase b (AKT) and mitogen-activated protein kinase (MAPK) signal pathways. PI3Ks were key regulators of intracellular signaling in response to the extracellular stimulators.…”
Section: Fto In Endometrial Cancermentioning
confidence: 99%